A repertoire of biomedical applications of noble metal nanoparticles - Azharuddin, Mohammad; Zhu, Geyunjian H.; Das, Debapratim; Ozgur, Erdogan; Uzun, Lokman; Turner, Anthony P. F.; Patra, Hirak K. (Royal Society of Chemistry, 2019)
Noble metals comprise any of several metallic chemical elements that are outstandingly resistant to corrosion and oxidation, even at elevated temperatures. This group is not strictly defined, but the tentative list includes ruthenium, rhodium, palladium, silver, osmium, iridium, platinum and gold, in order of atomic number. The emerging properties of noble metal nanoparticles are attracting huge interest from the translational scientific community and have led to an unprecedented expansion of research and exploration of applications in biotechnology and biomedicine. Noble metal nanomaterials can be synthesised both by top-down and bottom up approaches, as well as via organism-assisted routes, and subsequently modified appropriately for the field of use. Nanoscale analogues of gold, silver, platinum, and palladium in particular, have gained primary importance owing to their excellent intrinsic properties and diversity of applications; they offer unique functional attributes, which are quite unlike the bulk material. Modulation of noble metal nanoparticles in terms of size, shape and surface functionalisation has endowed them with unusual capabilities and manipulation at the chemical level, which can lead to changes in their electrical, chemical, optical, spectral and other intrinsic properties. Such flexibility in multi-functionalisation delivers ‘Ockham's razor’ to applied biomedical science. In this feature article, we highlight recent advances in the adaptation of noble metal nanomaterials and their biomedical applications in therapeutics, diagnostics and sensing.